Policy Reform in Indonesia and the Asian Development Bank's Financial Sector Governance Reforms Program Loan - George Abonyi (Asian Development Bank (ADB), 2005)
This paper presents a case study of the Asian Development Bank's Financial Sector Governance Reforms Development Program Loan (the Program) to the Government of Indonesia. The case study focuses on the political economy dimension of policy reform and its implications, rather than on Program details. Launched in June 1998, the Program was part of a multi-donor effort led by the International Monetary Fund, to help Indonesia respond to the Asian economic crisis and undertake reforms in the financial sector. The design and implementation of the Program took place in an environment characterized by an unexpected, deep, and sustained economic crisis, accompanied by social instability, and political and institutional uncertainty and change. Against this backdrop, the case study examines the context of Indonesia's policy reforms in the financial sector and the general design of the Program. It touches on the implementation of selected reforms and sustainability of the reform process. The purpose is to draw lessons that can assist in the more effective preparation and implementation of such reforms, and design of policy-based lending. In order to help structure the case study, a framework is introduced for the analysis of the political economy dimension of policy reform. This framework is proposed as a useful general tool both for the ex post understanding of the political economy dimension of policy reform, as well as an analytic tool for assisting in the ex ante design of specific policy reform programs and related policy-based lending.
hdl:11540/1906
Keywords: 330; Wirtschaftsreform; Agrarreform; Entwicklungsbank; Entwicklungsplanung; Kritik; Indonesien